Streptococcus mutans Secreted Products Inhibit Candida albicans Induced Oral Candidiasis - dos Santos, Jéssica Diane [UNESP]; Fugisaki, Luciana Ruano de Oliveira [UNESP]; Medina, Rebeca Previate [UNESP]; Scorzoni, Liliana [UNESP]; Alves, Mariana de Sá [UNESP]; de Barros, Patrícia Pimentel [UNESP]; Ribeiro, Felipe Camargo [UNESP]; Fuchs, Beth Burgwyn; Mylonakis, Eleftherios; Silva, Dulce Helena Siqueira [UNESP]; Junqueira, Juliana Campos [UNESP] (Frontiers, 2020)
In the oral cavity, Candida species form mixed biofilms with Streptococcus mutans, a pathogenic bacterium that can secrete quorum sensing molecules with antifungal activity. In this study, we extracted and fractioned culture filtrate of S. mutans, seeking antifungal agents capable of inhibiting the biofilms, filamentation, and candidiasis by Candida albicans. Active S. mutans UA159 supernatant filtrate components were extracted via liquid-liquid partition and fractionated on a C-18 silica column to resolve S. mutans fraction 1 (SM-F1) and fraction 2 (SM-F2). We found anti-biofilm activity for both SM-F1 and SM-F2 in a dose dependent manner and fungal growth was reduced by 2.59 and 5.98 log for SM-F1 and SM-F2, respectively. The SM-F1 and SM-F2 fractions were also capable of reducing C. albicans filamentation, however statistically significant differences were only observed for the SM-F2 (p = 0.004). SM-F2 efficacy to inhibit C. albicans was confirmed by its capacity to downregulate filamentation genes CPH1, EFG1, HWP1, and UME6. Using Galleria mellonella as an invertebrate infection model, therapeutic treatment with SM-F2 prolonged larvae survival. Examination of the antifungal capacity was extended to a murine model of oral candidiasis that exhibited a reduction in C. albicans colonization (CFU/mL) in the oral cavity when treated with SM-F1 (2.46 log) and SM-F2 (2.34 log) compared to the control (3.25 log). Although both SM-F1 and SM-F2 fractions decreased candidiasis in mice, only SM-F2 exhibited significant quantitative differences compared to the non-treated group for macroscopic lesions, hyphae invasion, tissue lesions, and inflammatory infiltrate. Taken together, these results indicate that the SM-F2 fraction contains antifungal components, providing a promising resource in the discovery of new inhibitors for oral candidiasis.
Keywords: biofilm; Candida albicans; filamentation; oral candidiasis; Streptococcus mutans